In volo con l'occhio termico - De Angelis, Emanuele; Giulietti, Fabrizio; Turci, Matteo; Amici, Stefania; Buongiorno, Maria Fabrizia (GEOmedia, 2012)
Il Laboratorio di Meccanica del Volo (MDVLab) dell'Università di Bologna nasce nel 2006 presso la Seconda Facoltà  di Ingegneria e la sua attività di ricerca riguarda principalmente problematiche di modellazione, simulazione e controllo del volo atmosferico e spaziale. Un'intensa collaborazione con l'Istituto Nazionale di Geofisica e Vulcanologia (INGV) ha consentito di estendere le proprie conoscenze al di fuori del settore aerospaziale, presentando oggi un'ampia offerta di tecnologie per l'Osservazione della Terra nell'ambito di progetti in cui MDVLab è coinvolto insieme ad INGV per l'impiego di velivoli non abilitati per applicazioni di gestione del rischio sismico, vulcanico ed ambientale. Flight testing with thermal camera Remote sensing from satellites or aircraft represents an impor-tant tool for the monitoring and management of catastrophic events. For some rapidly evolving phenomena (e.g. volcanic events, wildfires) they both show two relevant limits: long revisiting time (satellites) and the high cost and high human risk for monitoring. Unmanned Aircraft Veicle (UAV) because of their autonomous flight and real time telemetry transmis-sion offer a good solution to these limitations.To explore the operational aspects of such UAV deployments for example in volcanology, INGV in partnership with MavLab department of University of Bologna (Unibo) developed a UAV system and actually are carrying on integration studies and testing of sci-entific payloads. The payload is thermal camera. it has a light weight of 67.5g while the spectral response is in the 7-14mi-cron spectral range. The integration activities, the on board installation and results of the first in flight thermal acquisition experiment realized on July 30 2011, in Italy, are presented.